The implementation of the competency-based approach in the algerian middle school : a tentative analysis of constraints and obstacles - BENABED, Ammar (University of Mostaganem, 2012)
The present dissertation is a tentative analysis to shed light on a number of obstacles and constraints which are likely to impede the attainment of learners’ competencies targeted by the Competency-Based Approach in the Algerian Middle School. Seven years after the implementation of the Competency-Based Approach, middle school teachers still face problems to adapt their teaching practices to the principles and objectives underlying the Competency-Based Approach. The possible reasons behind this impediment could be either the teachers’ lack of the mastery of the theoretical basis in connection with the approach, learners’ lack of motivation towards English Language Learning (ELL), or the inadequacy of the proposed didactic materials. Based on a field work including two questionnaires and a checklist administered to 400 4AM learners, 300 middle school teachers and 20 inspectors, the collected data demonstrate that the implementation of the CBA depends on an appropriate management of the practitioners’ training.
Keywords: Key words: Competency-Based Approach, Competence, Autonomy, Learner-centred Learning, Scaffolding, Motivation, Teaching/learning Strategies